20 Gbps operation of membrane-based GaInAs/InP waveguide-type p–i–n photodiode bonded on Si substrate. (25th January 2018) - Gu, Zhichen; Inoue, Daisuke; Amemiya, Tomohiro; Nishiyama, Nobuhiko; Arai, Shigehisa
Abstract: A GaInAs/InP waveguide-type p–i–n membrane photodetector is shown to be a strong candidate for on-chip optical interconnection. A responsivity of 0.95 A/W is estimated for a device length of 30 µm. The 3 dB cutoff frequency is measured to be 13.3 GHz at a reverse bias of 3 V, which is in good agreement with the observed clear eye opening pattern up to 20 Gbps for a non-return-to-zero signal. Moreover, a bit error rate of less than 1 × 10 −9 is obtained at data rates of 20 and 10 Gbps with input powers of −10 and −13 dBm, respectively.